Exploring Spirituality of Elders Relocating into Long-Term Care Facilities - Kai-Li Tsai; Pei-Fen J. Chang; Anila J. Mathew; Clarissa Richard (Scholarworks @ WMU, 2022)
Background: Spirituality is recognized as an important contributor to quality of life, particularly for older adults. Yet, limited research has been conducted to examine spirituality of older adults relocating to long-term care facilities (LTCFs). The intent of this mixed methods study was to cull data from a parent study to explore different aspects of spirituality among residents newly admitted to LTCFs. Method: Qualitative and quantitative data of six participants from a parent study including interviews and scores from the religious and existential well-being sections of the Spiritual Well Being Scale (SWBS) were analyzed and triangulated. Results: Descriptive analysis of the demographic data including age, gender, ethnicity, and spirituality scores was conducted. Emerging themes from the qualitative interviews included: hope/hopelessness for the future; sense of belonging in the LTCF; contentment/discontentment with life; and personal religious beliefs. These themes, in turn, were triangulated with and supported by the SWBS scores Conclusion: The findings have the potential of developing recommendations for spiritually-based interventions to facilitate successful relocation to LTCFs. Clinical implications for occupational therapy and future research are discussed.